Perancangan Media Pembelajaran Berbasis Game Edukasi Menggunakan Construct 2 - Yuditihwa, Adesia; Okra, Riri; Musril, Hari Antoni; Derta, Sarwo (Intellect : Indonesian Journal of Learning and Technological Innovation, 2023)
The aim of this research is to create a useful and efficient educational game-based learning media in informatics learning using Construct 2 software. This research is based on the discovery of the informatics learning process in class VII at SMP N 2 Ampek Angkek that the media used by teachers is limited to printed books. Teachers still predominantly use the lecture method and have not utilized other learning media so that students often feel bored and sleepy during the learning process. As a result, many students did not understand the learning material during the semester. This research uses the Research and Development (R&D) method with a development model using the Hannafin and Peck approach, there are 4 stages of needs analysis, design, development and implementation. The results of this research found that educational game-based learning media in informatics subjects using construct 2 in Android format can be easily used by students as learning media to help the process of understanding teaching material. The product test carried out by the researchers produced an average score based on the validity test. The practicality test obtained an average score of 0.91 in the very high category, the effectiveness test obtained an average score of 0.87 in the high effectiveness category, and the validity test obtained an average score of 0.95. The findings from the research are that the media designed is very valid, practical and effective so that it can help students understand informatics learning material and make it easier for students to study anywhere without having to carry books, just use a smartphone. Abstrak Tujuan penelitian ini untuk menciptakan sebuah media pembelajaran berbasis game edukasi bermanfaat dan efisien dalam pembelajaran informatika menggunakan software Construct 2. Penelitian ini didasari temukan pada proses pembelajaran informatika di kelas VII di SMP N 2 Ampek Angkek bahwa media yang digunakan guru hanya sebatas buku cetak saja. Guru masih dominan menggunakan metode ceramah dan belum memanfaatkan media pembelajaran lain sehingga siswa sering merasa bosan dan ngantuk ketika proses pembelajaran berlangsung. Akibatnya banyak diantar siswa tersebut tidak memahami materi pembelajaran selama semester berlangsung. Penelitian ini menggunakan metode Research and Development (R&D) dengan model pengembangan menggunakan pendekatan Hannafin dan Peck, terdapat 4 tahapan analisis kebutuhan, desain, pengembangan, dan implementasi. Hasil penelitian ini ditemukan bahwa media pembelajaran berbasis game edukasi pada mata pelajaran informatika menggunakan construct 2 dalam format android dapat digunakan dengan mudah siswa sebagai media pembelajaran dalam membantu proses pemahaman materi ajar. Uji produk yang dilakukan peneliti menghasilkan skor rata-rata berdasarkan uji validitas. Uji praktikalitas memperoleh skor rata-rata 0,91 dengan kategori sangat tinggi, uji efektivitas memperoleh skor rata-rata 0,87 dengan kategori efektivitas tinggi, dan uji validitas memperoleh skor rata-rata 0,95.  Temuan dari penelitian bahwa media yang dirancang sangat valid, praktis dan efektif sehingga dapat membantu siswa dalam memahami materi pembelajaran informatika dan memudahkan siswa dalam belajar dimana saja tanpa harus membawa buku cukup memanfaatkan smartphone.